The status of prolonged grief disorder in the international classification of diseases (ICD-11) - Belopavlović Radomir; Novović Zdenka (University Educons, Faculty of Sports and Tourism, Novi Sad, 2020)
Grief due to loss of a significant other is a universal experience. However, within a small, but a significant group of individuals, this process can last longer than the culturally expected period, and it can be associated with the intense distress, dysfunction, and higher rates of mortality and morbidity. Grief has been observed in the scientific literature as an adaptive reaction to loss, but also as a factor associated with major depressive disorder, generalized anxiety disorder, and post-traumatic stress disorder. Previous versions of diagnostic systems, namely DSM-IV and ICD-10, have allocated the phenomenon of prolonged grief as a condition that requires further research, or the condition that requires care. There is a recommendation not to give a diagnosis of a depressive episode because of the normative nature of the reaction to loss. In the new iterations of classification manuals, the ICD-11, this condition is classified as the Prolonged grief disorder. The rationale for change is found in the studies which suggest that this disorder is phenomenologically different from similar states. It aggregates different risk factors and consequences, as well as different treatment solutions. This paper will focus on the criteria of the disorder in the ICD-11 space, researches which mention diagnosis validity, implications, and a broader frame for conceptual and clinical utility of this disorder.